Ectopic tooth involving the orbital floor and infraorbital nerve - Barbieri, D.; Capparè, P.; Gastaldi, G.; Trimarchi, M. (Journal of Osseointegration, 2017)
Aim Ectopic eruption of a tooth within the dental arch is often noticed in clinical practice and is well documented in the literature, while ectopic eruption outside the dental arch (as in the maxillary sinus) is rare. Due to its rarity and lack of consensus over management, its incidence needs to be further defined. Surgical approach, with cyst enucleation, has been considered the treatment of choice. In the present study, a case of an ectopic maxillary third molar with chronic purulent maxillary sinusitis is presented. The aim of this report is to describe the extraction of an ectopic third molar carried out through a nasal endoscopic procedure.